Development Strategies of Traditional Food as a Culinary Tourism Attraction in Pekalongan City: A SWOT-Based Qualitative Study - Kamila Abida Meha; Nurbaeti; Fetty Asmaniati; Elda Nurmalinda (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2026)
Purpose of the study: This research aims to identify the potential of traditional foods as a key element in the development of culinary tourism in the city of Pekalongan. The study was conducted in two districts, East Pekalongan and West Pekalongan, which are known to have significant culinary tourism potential. Design/methodology: This research employs a qualitative approach with data collection techniques including documentation studies, observation, and semi-structured interviews with various stakeholders, including local government officials, food vendors, and tourists. The SWOT analysis conducted reveals several strengths, such as the rich variety of unique and authentic traditional cuisines and strong cultural support. Weaknesses include ineffective promotion and limited supporting infrastructure for tourism. Opportunities are identified in the growing interest of tourists in culinary tourism and potential collaborations with the private sector. Threats include competition with other culinary tourism destinations and changing tourist preferences. Findings: The results show that traditional foods in Pekalongan play a significant role in attracting tourists and have a positive impact on the local economy. The main challenges in developing and marketing traditional foods as a culinary tourism attraction include insufficient promotion, limited infrastructure, and low community participation. The level of involvement and support from the local government and the community needs to be increased to optimize the potential of culinary tourism based on traditional foods. Research limitations/Implications: Based on these findings, appropriate strategies for culinary tourism development include enhancing promotion, strengthening infrastructure, and increasing community involvement. Novelty/Originality of the study: This study is novel in its focused examination of traditional foods in Pekalongan as a strategic, place-based asset for culinary tourism development in East and West Pekalongan, integrating stakeholder perspectives and SWOT analysis to reveal the gap between rich culinary heritage and its currently limited tourism optimization.